ANALISIS KOMPREHENSIF: SOSIALISASI SEBAGAI DETERMINAN DAN PARTISIPASI SEBAGAI MANIFESTASI DALAM KEHIDUPAN BEROLAHRAGA - Yan Indra Siregar; Putra Arima; Sidiq, Fajar; Tiara Chandra Sari Harefa; Eko Ginta Reja Tarigan; Mario Carolus Sembiring (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Sport is a social activity that has a significant influence on character development, health, and social interactions in society. In sports, socialization is a major factor determining a person's interest in and behavior toward sports activities, while sports participation is a concrete manifestation of this socialization process. This article aims to analyze the relationship between socialization as a determinant and participation as a manifestation in sports life. The research method used is a literature study with a qualitative descriptive approach through a review of various journals, books, and scientific articles. The results of the discussion indicate that family, school environment, peers, mass media, and community culture play a significant role in shaping a person's sports behavior. Sports participation is influenced by social, economic, educational, facilities, and individual motivational factors. With good sports socialization, the level of community participation in sports activities can increase, thus positively impacting community health and quality of life.